2010
DOI: 10.1111/j.1755-3768.2008.01450.x
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve hypoplasia in North America: a re‐appraisal of perinatal risk factors

Abstract: Purpose The purpose of this study is to describe and clarify the birth and prenatal characteristics of a large cohort of children with optic nerve hypoplasia. Methods This is a descriptive report of 204 patients aged ≤ 36 months and enrolled in a prospective study at the Children’s Hospital Los Angeles. Birth characteristics, including complications, were abstracted from study files and medical records. Systematic maternal interviews were conducted to obtain detailed prenatal histories. National birth data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 39 publications
2
56
0
Order By: Relevance
“…A Swedish study in optic nerve hypoplasia performed by Tornquist et al [26] demonstrated increased maternal smoking, young maternal age, preterm delivery and first parity as risk factors for optic nerve hypoplasia, whereas Garcia-Filion et al [13] demonstrated reduced maternal age, primiparity and increased caesarean section rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A Swedish study in optic nerve hypoplasia performed by Tornquist et al [26] demonstrated increased maternal smoking, young maternal age, preterm delivery and first parity as risk factors for optic nerve hypoplasia, whereas Garcia-Filion et al [13] demonstrated reduced maternal age, primiparity and increased caesarean section rate.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to previous epidemiological studies, this represents the largest cohort of SOD patients (n = 88), as many other cohorts also include optic nerve hypoplasia along with SOD [6,13,25]. We maximised ascertainment by systematically investigating all patients with optic nerve hypoplasia and also MPHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, premature infants (average gestational age 30.1±4.7 weeks) comprised the majority of De Silva's patient sample from a neonatal intensive care unit. Prematurity, uncommon in ONH (11%), 15 was present in just under 7% (n ¼ 1) of our study sample. Contrary to our study methods, the findings by De Silva et al 6 were not based on repeat measurements within the same subjects or at different time points; rather, the infants' measurements were compared with normal adult measurements, despite the cohort's prematurity.…”
Section: Discussionmentioning
confidence: 99%